553 Telemedicine trends during the COVID-19 pandemic – World Trade Center Health Program, 2020–2021 - Alejandro Azofeifa; Ruiling Liu; Hannah Dupont (Journal of Clinical and Translational Science)
Objectives/Goals: The World Trade Center (WTC) Health Program (Program), a limited federal healthcare program for eligible people exposed to the terrorist attacks on September 11, 2001, expanded telemedicine services during the COVID-19 pandemic. We analyzed service use trends from 2020–2021 to describe how the program implemented telemedicine services. Methods/Study Population: We estimated use rates of telemedicine-eligible services and telemedicine services by all included program members and by subgroups of members defined by member type (responder or survivor) and selected characteristics for the study period 2020–2021. We described the use trends of total telemedicine-eligible visits, telemedicine visits, and in-person visits, respectively, by quarter. We calculated the quarterly rates of telemedicine use per 1000 living members. We used a multivariable logistic regression to examine associations between member characteristics and telemedicine use rates. Results/Anticipated Results: About 75% of telemedicine visits were related to mental health services. In the second quarter of 2020 (April–June), telemedicine use rate (367 visits/1000 members) increased, exceeding in-person service rate (152 visits/1000 members) by 1.4 fold. Telemedicine use rate decreased gradually in the rest of the study period but still represented 38% of total visits by the end of 2021. Regression models showed differences in telemedicine use rates by member type and by demographic characteristics. Survivor members (vs. responder members), those self-identified as non-Hispanic Other races (vs. non-Hispanic White), those with preferred non-English language (vs. preferred English), and those not living in the New York metropolitan area (vs. living in the New York metropolitan area) were less likely to use telemedicine. Discussion/Significance of Impact: The expansion of telemedicine service provided members uninterrupted access to necessary health services during the COVID-19 pandemic. It underscored the importance of extensive partner collaboration, the capacity to rapidly develop necessary technical guidance, and the flexibility to timely address frequent regulatory guidance updates.